Do Climate Shocks Disadvantage Household Investment in Human Capital in Benin? An Approach Based on the Endogenous Treatment Regression Model - Logozo, Christian Duhamel; Kougblenou Menou, Vihoutou Médjikoue Marthe; Hekponhoue, Sylvain (European Scientific Journal, ESJ, 2024)
The increasing number of drought and flood shocks in Benin is causing considerable economic losses and social disruption. This article looks specifically at the effects of these shocks on household human capital expenditure in three climatic zones of Benin to highlight the effects specific to each zone. The data used come from the Harmonized Survey of Household Living Conditions. A linear regression model of the endogenous treatment was used for the analyses. The findings indicate that climate shocks reduce household capital expenditure and that this impact depends on the household’s climatic zone of residence. Investment in resilient infrastructure, such as water drainage and anti-flood systems, is suggested. The implementation of social and health assistance measures and school subsidies to cushion the impact of climatic shocks on the human capital expenditure of disaster-stricken households. The development and maintenance of an early warning system to anticipate the occurrence of shocks, floods, and droughts would also contribute to mitigation actions.